Winder Control Using a Ward-Leonard System - Whalley, Robert (2010)
An electrically driven winder for a deep shaft mine is considered. The system comprises a two stage Ward-Leonard motor-generator set, a winding drum, head and reduction gear and a braking unit, for which a linear model is derived. A minimum control effort regulation strategy is proposed enabling the simultaneous regulation of the motor speed and armature current. The computed responses for the system are presented for open and closed loop conditions. The effectiveness of the system when following particular, demanded speed requirements is investigated. The control energy dissipation and regenerative braking performance of the system are commented upon.